What they understand is not necessarily important to practice: Exploring halal literacy learning in high school students - Iis Aisyah; Dian Friantoro; Muhammad Dzulfaqori Jatnika (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Halal literacy has not become an important thing for high school students. Even though high school students or teenagers, in the future, will be the main consumers of halal products in Indonesia. The purpose of this study is to determine the Halal Literacy Index in high school students using the level of approval and the level of importance to be practiced. This study uses a quantitative descriptive approach. The respondents studied were 334 high school students in Tasikmalaya, West Java. The results showed that high school students have a higher level of approval than the level of importance to practice. It was found that of all the items, the student's level of approval has an average of 4.327 so it falls into the